Does a Flexible Parental Leave System Stimulate Maternal Employment? - Lennart Ziegler; Omar Bamieh (Institute of Labor Economics (IZA), 2023)
This study examines the effect of two recent parental leave reforms in Austria that allow parents to choose leave schemes with varying duration. Using a regression discontinuity design, we find that the introduction of more flexible scheme choices led mothers to take, on average, 1-2 months less of leave. This decrease in leave duration, however, was not accompanied by an employment increase of similar magnitude. To understand the absence of labor supply effects, we examine data on work preferences from the Austrian Microcensus. Child care duties are cited as the primary reason for not seeking work but few mothers indicate that they would start working if better access to formal childcare were available. Switching to the more flexible leave system had a minimal effect on the labor market choices of mothers, as the majority continue to prioritize child care responsibilities and do not consider nurseries as a desirable alternative.
Keywords: J12; J13; J18; J22; I38; 330; parental leave; gender differences; child care; financial incentives; labor supply; return to work